2016
DOI: 10.3390/ijms17060937
|View full text |Cite
|
Sign up to set email alerts
|

N-Glycosylation of Human R-Spondin 1 Is Required for Efficient Secretion and Stability but Not for Its Heparin Binding Ability

Abstract: R-spondin 1 (Rspo1) plays an essential role in stem cell biology by potentiating Wnt signaling activity. Despite the fact that Rspo1 holds therapeutic potential for a number of diseases, its biogenesis is not fully elucidated. All Rspo proteins feature two amino-terminal furin-like repeats, which are responsible for Wnt signal potentiation, and a thrombospondin type 1 (TSR1) domain that can provide affinity towards heparan sulfate proteoglycans. Using chemical inhibitors, deglycosylase and site-directed mutage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
7
0
1
Order By: Relevance
“…While RSPO1 induced the wild type promoter-luciferase in a dose-dependent manner, it could not activate the reporter with CRE mutations ( TGcCAgCA ) ( Figure 6e ), rendering its specificity. In addition, we co-expressed ESR1 -luciferase with RSPO1-FL (full length), RSPO1-N137Q (a mutated form with compromising secretion) ( Chang et al, 2016 ), RSPO1 F110A/F106A (unable to bind LGR4) ( Wang et al, 2013 ), and RSPO1 R66A/Q71A (binds to LGRs but is unable to amplify Wnt signaling) ( Xie et al, 2013 ). RSPO1-FL and RSPO1 R66A/Q71A were able to activate the luciferase activities, but RSPO1-N137Q and RSPO1 F110A/F106A could not ( Figure 6f ), suggesting the secretion of Rspo1 and its association to LGR4 are critical for Esr1 transcription.…”
Section: Resultsmentioning
confidence: 99%
“…While RSPO1 induced the wild type promoter-luciferase in a dose-dependent manner, it could not activate the reporter with CRE mutations ( TGcCAgCA ) ( Figure 6e ), rendering its specificity. In addition, we co-expressed ESR1 -luciferase with RSPO1-FL (full length), RSPO1-N137Q (a mutated form with compromising secretion) ( Chang et al, 2016 ), RSPO1 F110A/F106A (unable to bind LGR4) ( Wang et al, 2013 ), and RSPO1 R66A/Q71A (binds to LGRs but is unable to amplify Wnt signaling) ( Xie et al, 2013 ). RSPO1-FL and RSPO1 R66A/Q71A were able to activate the luciferase activities, but RSPO1-N137Q and RSPO1 F110A/F106A could not ( Figure 6f ), suggesting the secretion of Rspo1 and its association to LGR4 are critical for Esr1 transcription.…”
Section: Resultsmentioning
confidence: 99%
“…All 4 R-spondins have a common TSP domain, which mediates glycosaminoglycan binding. [59][60][61] To further study the functional role of R-spondin interaction with HS, we employed a mutant R-spondin (R-spondin-ΔTSP)lacking the TSP domain and C-terminal basic amino acid-rich domain. As a control, we used R-spondin lacking the basic amino acid-rich domain only (R-spondin-ΔAA).…”
Section: Loss Of Hs Attenuates Cell-surface Binding Of Wnt3a and R-spmentioning
confidence: 99%
“…All 4 R-spondins contain a TSP domain that can bind to HSPGs/ heparin. 60,61,65 Deletion of the TSP domain of R-spondin resulted in a reduced capacity to promote Wnt signaling in MM. Activation of Wnt signaling by this TSP domain-deficient R-spondin mutant was markedly reduced and was no longer dependent on cell-surface HS expression.…”
Section: R-spondin Family Proteins Have Recently Been Identified As Imentioning
confidence: 99%
“…For example, it was shown that the Nglycosylation of human Rspo1 at Asn137 (which is a residue located at the C-terminus of the Fu2 domain of this protein and is predicted to be disordered, being characterized by the mean disorder score of 0.53) is required for the efficient secretion and stability of this protein, but does not play a role in interaction of Rspo1 with heparin sulfate proteoglycans. 62 A single phosphorylation site (Thr253) is located within the disordered C-tail of human Rspo1. Since this site is positioned within one of the MoRFs, it is likely that it plays a role in regulation of the disorder-based interactivity of this protein.…”
Section: R-spondinmentioning
confidence: 99%
“…In fact, similar to Rspo1, human Rspo2 can undergo Nglycosylation, which is important for secretion and stability of this protein. 62 Curiously, although Nglycosylation of Rspo2 was shown to occur at Asn160, a position near the N-terminus of TSR1 domain, it did not affect the heparin binding capability of this protein, 62 a rather unexpected outcome since the TSR domain is known to be responsible for interaction with heparin sulfate proteoglycans (HSPGs). 55 Therefore, it seems that similar to the functional importance of long IDPRs on the intracellular side for mediating protein-protein interactions and/or PTMs, extracellular proteins might use their long IDPRs to carry PTM sites and sites of protein-protein interactions.…”
Section: R-spondins 2 3 Andmentioning
confidence: 99%